Polycarpaea palakkadensis (Caryophyllaceae), a new species from Kerala, South-West India - Arya, Sindhu; Kumar, Venugopalan Nair Saradamma Anil; Nathanpillai, Ambika Viswa; Philip, Alen Alex; Sojan, Jose; Suresh, Veerankutty (Phytotaxa, 2021)
Polycarpaea palakkadensis, a new species of Caryophyllaceae from the hillocks of Palakkad District (Kerala, India) is described and illustrated. P. palakkadensis is morphologically similar to P. rangaiahiana from which differs in having fused ovate bracts, capilliform bracteoles, linear stipules, ovate-cordate petals, filaments much shorter than anther, capsule with 1–2 ovoid elliptical seeds.